2020
DOI: 10.3390/nu12030632
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacillus Spores Protect Against Acetaminophen Induced Acute Liver Injury in Rats

Abstract: Acetaminophen (APAP) is one of the most used analgesics and antipyretic agents in the world. Intoxication with APAP is the main cause of acute liver toxicity in both the US and Europe. Spore-forming probiotic bacteria have the ability to resist harsh gastric and intestinal conditions. The aim of this study was to investigate the possible protective effect of Bacillus (B) species (sp) spores (B. licheniformis, B. indicus, B. subtilis, B. clausii, B. coagulans) against hepatotoxicity induced by APAP in rats. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 39 publications
3
38
0
1
Order By: Relevance
“…Meanwhile, Sharma et al reported that probiotic Enterococcus lactis IITRHR1 and Lactobacillus acidophilus MTCC447 protect against APAP-induced liver injury by modulating the antioxidant capacity of the liver and the expression of key apoptotic/anti-apoptotic proteins (Sharma et al, 2011 ). MegaSporeBioticTM probiotic capsules are composed of a probiotic blend of spores from five Bacillus species that improve the histopathological hepatic injury and decreased the level of proinflammatory cytokines, indicating that Bacillus spa spores have a protective effect on acute hepatic injury induced by APAP (Neag et al, 2020 ). This data is significant for the treatment of ALI and we also need to further explore whether the pretreatment of probiotics could improve the detoxification ability and antioxidant capacity of hepatocytes.…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
“…Meanwhile, Sharma et al reported that probiotic Enterococcus lactis IITRHR1 and Lactobacillus acidophilus MTCC447 protect against APAP-induced liver injury by modulating the antioxidant capacity of the liver and the expression of key apoptotic/anti-apoptotic proteins (Sharma et al, 2011 ). MegaSporeBioticTM probiotic capsules are composed of a probiotic blend of spores from five Bacillus species that improve the histopathological hepatic injury and decreased the level of proinflammatory cytokines, indicating that Bacillus spa spores have a protective effect on acute hepatic injury induced by APAP (Neag et al, 2020 ). This data is significant for the treatment of ALI and we also need to further explore whether the pretreatment of probiotics could improve the detoxification ability and antioxidant capacity of hepatocytes.…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
“…B. clausii inhibited secretion of pro-inflammatory cytokines and reactive oxygen species production in rotavirus-infected cells (39). It was demonstrated that pretreatment with probiotic capsules of Bacillus species spores caused a significant decrement in pro-inflammatory cytokines (42). Treatment with B. clausii UBBC07 importantly attenuated oxidative stress by increasing catalase and SOD, and decreasing MDA in acetaminophen-induced uremia in rats (43).…”
Section: Discussionmentioning
confidence: 99%
“…Many B. licheniformis strains were proved to have the ability to alleviate in ammatory response in vitro and in vivo One study has demonstrated that B. licheniformis strain can signi cantly decrease production of the pro-in ammatory cytokines (IL-8) under the challenge of Salmonella enterica serovar Typhimurium in intestinal epithelial cells [38]. Pretreatment with Bacillus species spores (B. licheniformis, B. indicus, B. subtilis, B. clausii, and B. coagulans) lowered the serum levels of pro-in ammatory cytokines (TNF-α and 1L-1β) against acetaminophen-induced acute liver injury in rats [41]. Similarly, we found that B. licheniformis PF9 treated with pathogenic exposure at the ratios of 1:10, 1:25, 1:50, or 1:100 (ETEC F4 to B. licheniformis PF9) actually attenuated the release of cytokines IL-8 (Fig.…”
Section: Discussionmentioning
confidence: 99%